A simple predictive formula for the blood requirement in patients with high‐energy blunt injuries transferred within one hour post‐trauma. Issue 2 (20th October 2014) - Akasaki, Yukio; Sugimori, Hiroshi; Momii, Kenta; Akahoshi, Tomohiko; Matsuura, Suguru; Iwamoto, Yukihide; Maehara, Yoshihiko; Hashizume, Makoto
<x xml:space="preserve">Abstract</x> Aims To recognize patients who require massive transfusion at the early stage of blunt trauma, we retrospectively investigated patients with high‐energy blunt injuries transferred within 1 h post‐trauma. Methods Between August 2007 and July 2011, 233 trauma patients were: (i) injured by a high‐energy blunt mechanism with Injury Severity Score ≥9; (ii) not dead on arrival; (iii) older than 9 years; and (iv) at our center within 1 h after injury. The findings for 113 of those patients were analyzed, including those produced by ultrasonography, computed tomography, and arterial blood gas analyses. Results Of 113 patients, 33 underwent massive transfusion (≥6 units) within 8 h of arrival. A logistic regression analysis revealed that an arterial lactate level ≥28 mg/dL (P < 0.001; odds ratio, 105.11; 95% confidence interval, 12.58–2, 718.84) and a flat ratio of the inferior vena cava on computed tomography ≥3 (P < 0.001; odds ratio, 32.50; 95% confidence interval, 4.44–714.44) were significant independent predictors for a massive transfusion within 8 h. In a receiver operating curve analysis, the area under the curve of the need for massive transfusion was 0.956, with a sensitivity of 0.94 and a specificity of 0.90. A linear predictive formula for the probability (P) of receiving a massive transfusion was generated as P = 2 × lactate (mg/dL) + 15 × the flat ratio of inferior vena cava − 103. Using another 52 trauma patients, the formula was validated. Conclusions An elevated level of arterial lactate and the flat ratio of inferior vena cava were significant predictors for identifying the patients who would require a massive transfusion in the early stage after high‐energy blunt trauma.